Strategi Guru Dalam Menanamkan Nilai-Nilai Gotong Royong Melalui Pembelajaran SBDP (Seni Musik) Pada Murid Kelas III di SD Yayasan IBA Palembang - Dhea Azzahra Putri; Tutut Handayani; Agra Dwi Saputra; Mardiah Astuti; Muhamad Afandi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Mutual cooperation which is an important part of strengthening character education. However, in fact, the value of mutual cooperation is beginning to erode due to the influence of individualism that is getting stronger. Therefore, the value of mutual cooperation in schools, especially elementary schools, needs to internalize this value from an early age. This study aims to describe teachers' strategies in instilling the values of mutual cooperation through SBdP (Music Arts) learning in Grade III students at Yayasan IBA Palembang Elementary School. This study uses a qualitative approach with a descriptive type of research. The subjects of the study include Music Arts teachers, grade III students, and school principals. Data collection techniques are carried out through observation, interviews, and documentation to obtain comprehensive data. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data is tested through triangulation of sources and techniques. The results of the study show that teachers' strategies in instilling the values of mutual cooperation through SBdP lessons, especially in music arts for grade III students, are carried out through various ways ranging from learning strategies, learning media, and learning evaluation. Supporting factors in the implementation of the strategy include students, parental support, and school support, inhibiting factors include limited learning time, experience playing music, and differences in students' character and social attitudes. Grade III students already have a good character of mutual cooperation seen from togetherness, please help, unity, socialization and family. Based on these findings, it can be concluded that teacher strategies that are designed in a planned and consistent manner are able to instill the values of mutual cooperation in elementary school students. This research can inspire elementary school teachers in instilling the values of mutual cooperation.